Proportion of Variant Anatomy of the Circle of Willis and Association with Vascular Anomalies on Cerebral CT Angiography - Roy Munialo Machasio; Rose Nyabanda; Timothy Musila Mutala (Radiology Research and Practice)
Background and Purpose. There is a wide variation in the anatomy of the CW in different individuals and population groups. The purpose of this study was to determine the proportion of variant anatomy of the circle of Willis (CW) and associated anomalies in patients with suspected cerebrovascular disease referred for cerebral computed tomography angiography (CTA) in two tertiary hospitals in Kenya. Methodology. This was a cross-sectional descriptive study conducted on 94 patients referred for cerebral CTA at the Kenyatta and Nairobi hospitals from August 2017 to February 2018. MIP and 3D reformatted images were analyzed by two senior radiologists to determine the final configuration of the CW and presence of vascular pathology. Vessels with diameters <0.8 mm were considered to be absent or hypoplastic. Chen et al. classification was used to determine the final configuration of CW. Results. Complete CW was seen in 37.2% (37.7% vs. 36.6% in males and females, respectively, p=0.909). Type A variant was the commonest anterior variant at 78.7%. Type E variant was the dominant posterior variant at 41.5%. Fetal PCA was demonstrated in 25.5%, unilateral > bilateral fetal PCA. Aneurysms were seen in 24.5% of patients. ACoA aneurysms were commonest at 43.6%. AVMs were seen in 8.5% of patients. Azygous ACA, fenestration, and duplication of vessels and persistent TA were not demonstrated. There is no significant association between aneurysms/AVMs and CW configuration. Conclusion. The findings in this study demonstrate slight differences in the CW configuration. A higher proportion of complete anterior CW was seen in female patients. Type A anterior and type E posterior circulation variants were the commonest in both males and females. No significant association was demonstrated between CW configuration and occurrence of aneurysms/AVMs in this study. Various methods of classification of CW configuration have been proposed with no standardized method to date, thus the need for consensus building between neuroanatomists, neurologists, neurosurgeons, and neuroradiologists for ease of comparison between similar future studies on the CW.